Mathematical Thinking Processes of Junior High School Students in Solving Contextual Problems Based on Learning Styles - Setiyani Setiyani; Marwia Tamrin Bakar; Nurul Ikhsan Karimah; Sri Sumarwati (Department of Mathematics Education Program IPI Garut, 2026)
Masalah kontekstual menuntut proses berpikir matematis yang runtut, logis, dan reflektif. Penelitian ini bertujuan menganalisis proses berpikir matematis siswa dalam menyelesaikan masalah kontekstual berdasarkan kerangka Mason (tahap entry, attack, dan review) ditinjau dari gaya belajar. Menggunakan pendekatan kualitatif deskriptif, penelitian ini melibatkan siswa kelas VII SMP Negeri di Kota Cirebon. Tiga subjek dipilih secara purposif untuk mewakili gaya belajar visual, auditori, dan kinestetik. Data dikumpulkan melalui tes, angket gaya belajar, dan wawancara mendalam. Hasil menunjukkan perbedaan karakteristik berpikir: siswa visual memenuhi seluruh indikator pada semua tahapan; siswa auditori mampu pada tahap entry dan attack namun terbatas dalam mengembangkan solusi pada tahap review; sedangkan siswa kinestetik hanya memenuhi sebagian indikator dan kesulitan dalam justifikasi serta refleksi. Temuan ini menegaskan pengaruh gaya belajar terhadap kualitas proses berpikir matematis. Implikasinya, pembelajaran matematika perlu dirancang secara adaptif untuk memperkuat penalaran dan refleksi siswa sesuai karakteristik belajarnya. Contextual problems in mathematics require a mathematical thinking process that is coherent, logical, and reflective. This study aims to analyze students' mathematical thinking processes in solving contextual problems based on Mason’s framework—comprising the entry, attack, and review phases—viewed through learning styles. Utilizing a descriptive qualitative approach, the study involved seventh-grade students at a state junior high school in Cirebon. Three subjects were purposively selected to represent visual, auditory, and kinesthetic learning styles. Data were gathered through mathematical thinking tests, learning style questionnaires, and in-depth interviews. The results reveal distinct characteristics: visual learners met all indicators across all phases; auditory learners succeeded in the entry and attack phases but struggled with developing alternative solutions during the review phase; while kinesthetic learners only met partial indicators and faced difficulties in providing justification and reflection. These findings underscore the influence of learning styles on the quality of mathematical thinking. Consequently, mathematics instruction should be adaptively designed to strengthen student reasoning and reflection according to their learning characteristics.